Use the power you have : a brown woman's guide to politics and political change - Jayapal, Pramila, 1965- (The New Press, 2020)
-- all Written with passion and insight, Use the Power You Have offers a wealth of ideas and inspiration for a new generation of engaged citizens interested in fighting back and making change, whether in Washington or in their own communities.